Vasectomy of older bulls to manage elephant overpopulation in Africa: a proposal - Ben Bokhout; Marius Nabuurs; Jong, de (Pachyderm)
This article is a proposal based on literature, it provides a concept that still requires on the ground investigation and implementation. When it was initially presented at the EMOA symposium in 2004 vascetomy had not yet performed on a bull elephant, but since tht time the opertion has been carried out several times in South Africa. The article reviews the advantages of male sterilization over that of females and looks at the 'general, technical, sex-related and financial aspects of the vascetomy of elephant bulls'. It appears that after dominant bulls are selected, treatment of less that 2% of the elephants would stabilize a population in parks with a natural population growth rate. Analysis suggests that for parks with 100 to 300 elephants, occasional vasectomy of a dominant bull would provide an effective elepahnt family planning tool.